1995
DOI: 10.1016/s1055-3290(05)80014-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to getting published: Results of the JANAC survey

Abstract: In order to identify strategies to promote the publication of ANAC members' knowledge and expertise, the authors conducted a survey of JANAC readers. Twenty-four respondents, almost all clinicians, identified 25 areas of interest they want to develop for publication. Barriers to getting published fell into four categories: lack of time, writing skills, self-confidence, and motivation or ideas. Suggestions for facilitating scholarship focused mainly on collaboration with writing experts and learning through edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…For clinicians who are actively involved in the research process, clinical settings may not be conducive to research. Lack of time, writing skills, self‐confidence, academic support, motivation and inspiration compromise research productivity [27], but can be overcome by encouraging a research culture. For example, by creating an academic culture and providing infrastructure, one academic centre without any National Institute of Health grants became one of America's top 20 centres [28].…”
Section: Barriers To Obtaining High‐quality Evidencementioning
confidence: 99%
“…For clinicians who are actively involved in the research process, clinical settings may not be conducive to research. Lack of time, writing skills, self‐confidence, academic support, motivation and inspiration compromise research productivity [27], but can be overcome by encouraging a research culture. For example, by creating an academic culture and providing infrastructure, one academic centre without any National Institute of Health grants became one of America's top 20 centres [28].…”
Section: Barriers To Obtaining High‐quality Evidencementioning
confidence: 99%
“…Fonteyn (1997) noted that myths often exist in writing for publication and include those related to publication delays. Myths may operate as barriers or excuses that unnecessarily hinder success in publishing (Meisenhelder, Kalinoski, & Saunders, 1995). Authors may wait months or even years after identifying a clinical idea or completing research to write their manuscripts.…”
Section: Submission Delaymentioning
confidence: 99%
“…A recent survey indicated that one of the four reasons clinicians do not pursue publication is that they are unable to think of a strong idea that motivates them for publication 4 . Developing a strong idea (usually from clinical practice queries) is the first and most important stage in the publication process.…”
mentioning
confidence: 99%
“…Other noted barriers to publication include writing skills and confidence with the process of publication 4 . Peerreviewed manuscript publication requires technical writing skills that improve with practice 5 .…”
mentioning
confidence: 99%